2021
DOI: 10.1371/journal.pone.0253258
|View full text |Cite
|
Sign up to set email alerts
|

The cancer angiogenesis co-culture assay: In vitro quantification of the angiogenic potential of tumoroids

Abstract: The treatment response to anti-angiogenic agents varies among cancer patients and predictive biomarkers are needed to identify patients with resistant cancer or guide the choice of anti-angiogenic treatment. We present “the Cancer Angiogenesis Co-Culture (CACC) assay”, an in vitro Functional Precision Medicine assay which enables the study of tumouroid induced angiogenesis. This assay can quantify the ability of a patient-derived tumouroid to induce vascularization by measuring the induction of tube formation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 56 publications
0
5
0
1
Order By: Relevance
“…Besides matrix composition, an appropriate supportive cell type is important for endothelial cells to form stable pre-vascular networks. Fibroblasts have been widely used in angiogenesis models since they produce a supportive matrix [48] and have been shown to promote migration and proliferation of co-cultured HUVEC [49][50][51]. Fibroblasts have also been demonstrated to support hepatocytes, e.g.…”
Section: Development Of the Cfg Bioink Supporting Pre-vascular Networ...mentioning
confidence: 99%
“…Besides matrix composition, an appropriate supportive cell type is important for endothelial cells to form stable pre-vascular networks. Fibroblasts have been widely used in angiogenesis models since they produce a supportive matrix [48] and have been shown to promote migration and proliferation of co-cultured HUVEC [49][50][51]. Fibroblasts have also been demonstrated to support hepatocytes, e.g.…”
Section: Development Of the Cfg Bioink Supporting Pre-vascular Networ...mentioning
confidence: 99%
“…Previous evidence has demonstrated that up-regulation of genes encoding angiogenic factors correlates with the increased secretion of angiogenic factors from the cells [ 49 51 ]. Our present study also addressed this by using ELISA to measure the secreted levels of VEGF and TGF-β1 (the representatives for the up-regulated and unaffected angiogenic factors, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…In consistent with those previously reported findings, our present data confirmed that changes in expression of the angiogenesis-related genes really affected the secretion of their protein products. Among the secreted angiogenic factors, VEGF and FGF2 have been reported to trigger ECs activity [ 50 , 51 ]. Due to the up-regulation of VEGF and FGF2 in our present study, we thus performed in vitro experiments to assess the angiogenesis features induced by CM from MDCK cells with ARID1A and/or ACTB knockdowns.…”
Section: Discussionmentioning
confidence: 99%
“…Curiously, when HUVECs were themselves also incorporated into the spheroids, as a tri-culture of cancer cells, fibroblasts and HUVECs, the angiogenic potential of the spheroids were reduced compared to the co-cultures of only cancer cells and fibroblasts (Nashimoto et al, 2020). In addition, co-culture assays have been developed for quantification of angiogenesis that can be adapted to screen for novel anti-angiogenic compounds or even used in a personalized medicine context by screening known anti-angiogenic therapeutics against patient-derived tumor organoids Truelsen et al, 2021). Altogether, these co-culture models are a useful tool for studying angiogenesis as well as identifying effective therapeutics and underscoring the importance of multi-cellular interactions in this process.…”
Section: Vasculature and Angiogenesismentioning
confidence: 99%